Sulfone polymer porous membrane as well as preparation method and application thereof

Through reasonable preparation and preparation technology, the problems of low mechanical strength, insufficient water flux and low filtration accuracy of polyethersulfone microporous membranes are solved, and the high toughness, mechanical strength and water flux of the sulfone polymer porous membranes are achieved, which improves the Filtration accuracy and membrane service life.

CN119386689APending Publication Date: 2025-02-07HANGZHOU SHENGJU ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682202.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing polyethersulfone microporous membranes have problems such as low mechanical strength, insufficient water flux and low filtration accuracy in aqueous liquid filtration, and it is difficult to effectively control the pore size.

Method used

By reasonably preparing the cast film liquid of polyethersulfone resin, sulfonated polyethersulfone resin, alkyl amide, additive and nanozirconia powder, a sulfone polymer porous film is prepared to improve its hydrophilicity and mechanical strength, and through Specific preparation processes control pore size distribution.

Benefits of technology

The high toughness, mechanical strength and water flux of the sulfone polymer porous membrane are achieved, which improves the filtration accuracy and the service life of the membrane, while simplifying the production process and is suitable for continuous production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148626840000101
    Figure BDA0005148626840000101
  • Figure HDA0005148626850000011
    Figure HDA0005148626850000011
  • Figure HDA0005148626850000012
    Figure HDA0005148626850000012
Patent Text Reader

Abstract

The invention discloses a sulfone polymer porous membrane and a preparation method thereof. The sulfone polymer porous membrane comprises 5-30 parts of polyethersulfone resin, 3-15 parts of sulfonated polyethersulfone resin, 30-85 parts of alkylamide, 1-15 parts of an auxiliary agent and 0.1-5 parts of nano zirconium oxide powder. The preparation method of the sulfonated polyethersulfone resin comprises the following steps: adding polyethersulfone resin into dichloromethane, then adding chlorosulfonic acid at a certain stirring speed, and reacting for a certain time. The sulfone polymer porous membrane prepared by the method is high in toughness and mechanical strength, long in service life, narrow in pore size distribution and low in bubble point pressure, can be applied to the fields of biological medicines, food beverages, sewage treatment and the like, is suitable for high-viscosity solutions, is simple in process, is suitable for continuous production, and is relatively large and stable in water flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of filtration membrane materials, in particular to the field of IPC B01D71, and more specifically to a sulfone polymer porous membrane and a preparation method and application thereof. Background Art

[0002] Polyethersulfone is a comprehensive polymer membrane material with excellent heat resistance, alkali resistance, pressure resistance and other properties. It is a good material for preparing various microporous membranes. At present, polyethersulfone microporous membranes are mainly used for the filtration of aqueous liquids, but polyethersulfone resin itself is hydrophobic. Although the addition of polyvinylpyrrolidone will enhance its hydrophilicity, it will also lead to low mechanical strength. At the same time, in order to extend the service life of polyethersulfone microporous membranes, the mechanical strength of polyethersulfone resin is very important, but when the content of polyethersulfone resin is too little, it will also affect the mechanical strength of the membrane. Polyethersulfone resin is generally prepared by non-solvent phase separation method, which is not easy to control the pore size, resulting in low membrane mechanical strength, low water flux and low filtration accuracy, and at the same time, it may also damage the integrity of the membrane. Summary of the invention

[0003] In order to solve the above technical problems, the first aspect of the present invention provides a sulfone polymer porous membrane, the raw materials of which include 5-30 parts of polyethersulfone resin, 3-15 parts of sulfonated polyethersulfone resin, 30-85 parts of alkylamide, 1-15 parts of auxiliary agent, and 0.1-5 parts of nano zirconium oxide powder.

[0004] Preferably, in the raw material of the sulfone polymer porous membrane, the weight ratio of the polyethersulfone resin to the sulfonated polyethersulfone resin is 1.1-4:1.

[0005] The ether bonds contained in the polyethersulfone resin can affect the flexibility of the polymer and the fluidity of the melt. If the content of the polyethersulfone resin is too high, the density of the polymer chain in the casting solution will increase, affecting the pores and the interconnection between the pores, thereby reducing the pore size and reducing the water flux. If the content of the polyethersulfone resin is too low, it will affect the curing rate and reduce the toughness of the membrane. By adding 5-30 parts of polyethersulfone resin and 5-15 parts of sulfonated polyethersulfone resin, the hydrophilicity of the sulfone polymer porous membrane is improved. At the same time, under the action of alkylamide, additives, nano zirconium oxide powder, etc. in the system, the pores and the interconnection between the pores are improved, so that the toughness of the sulfone polymer porous membrane is enhanced.

[0006] The preparation method of the sulfonated polyethersulfone resin is as follows: adding the polyethersulfone resin into dichloromethane, then adding chlorosulfonic acid at a certain stirring rate, and reacting for a certain time.

[0007] Optionally, the preparation method of the sulfonated polyethersulfone resin is: adding 10-20 g of polyethersulfone resin into 100-300 mL of dichloromethane, then adding 10-20 mL of chlorosulfonic acid at a stirring rate of 600-1000 r / min, and reacting for 1-10 hours.

[0008] Preferably, the alkylamide includes at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

[0009] More preferably, the alkylamide is N,N-dimethylformamide.

[0010] The alkylamide in the membrane casting solution interacts with the polyethersulfone resin and the sulfonated polyethersulfone resin to improve the solubility of PES. Meanwhile, the precipitation speed of the membrane is appropriate, so that the water flux is increased.

[0011] Optionally, the auxiliary agent is at least one of polyethylene glycol, polypropylene glycol, polyethylene glycol bis(benzophenone)-2-carboxylate (CAS: 1246194-73-9), tetrahydrofuran and neopentyl glycol polymer (100493-52-5), polybutylene glycol, and a homopolymer of 2-furanmethanol (CAS: 25212-86-6); Optionally, the auxiliary agent is a homopolymer of PEG200 and 2-furanmethanol, and the weight ratio of the homopolymer of PEG200 and 2-furanmethanol is 1:1.

[0012] Preferably, the average particle size of the nano zirconium oxide powder is 10-50 nm.

[0013] More preferably, the average particle size of the nano zirconium oxide powder is 30 nm.

[0014] Optionally, the nano zirconium oxide powder is nano zirconium oxide powder modified by a silane coupling agent; in the present application, the silane coupling agent is KH570.

[0015] The raw material of the sulfone polymer porous membrane also includes 7-20 parts by weight of polyvinyl pyrrolidone, and the K value of the polyvinyl pyrrolidone is 27-33, namely PVP K30.

[0016] A specific amount of sulfonated polyethersulfone resin, polyvinyl pyrrolidone, and PEG200 are added to the raw materials for preparing the sulfone polymer porous membrane, thereby improving the interaction between the porous membrane and the solution to be filtered, including wetting speed, surface tension, etc. In particular, the sulfone polymer porous membrane is used in the medical field and can be quickly wetted by the drug solution, thereby reducing the formation of bubbles and the risk of blood reflux. In addition, the drug solution generates a strong surface tension between the drug solution and the membrane surface in the curved channel aperture.

[0017] The sulfone polymer porous membrane comprises an upper surface, a lower surface and a channel between the upper surface and the lower surface, wherein the channel is composed of a plurality of evenly distributed holes, and the holes are interconnected. The solution (such as filtrate, drug solution) flows in from the upper surface, passes through the channel to generate a siphon effect, and then flows out from the lower surface, thereby achieving a filtering effect.

[0018] In the prepared sulfone polymer porous membrane, the pore sizes of the upper surface and the lower surface have the following characteristics: the pores with pore sizes exceeding 10 microns account for 1-5% of the total number of pores, the pores with pore sizes of 5-10 microns account for 90-95% of the total number of pores, and the pores with pore sizes less than 5 microns account for the remainder of the total number of pores, wherein the total number of pores with pore sizes exceeding 10 microns, pores with pore sizes of 5-10 microns, and pores with pore sizes less than 5 microns is 100. The pore size of the sulfone polymer porous membrane is tested by a PMI pore size tester.

[0019] The sulfone polymer porous membrane prepared by the method has a uniform pore size distribution and high pore size consistency, so that molecules or particles of a specific size can be separated more effectively. During long-term use, it helps to maintain the performance of the membrane, reduce the degradation of separation performance caused by pore size changes, and improve the anti-pollution ability and service life of the membrane. It can be well used for drug release, separation of specific molecules, etc.

[0020] Preferably, the thickness of the sulfone polymer porous membrane is 80-150 μm; further, the thickness of the sulfone polymer porous membrane is 110-120 μm. The sulfone polymer porous membrane with a thickness of 110-120 μm can effectively filter and has high mechanical strength and filtration efficiency.

[0021] The second aspect of the present invention also provides a method for preparing the sulfone polymer porous membrane as described above, comprising the following steps:

[0022] (1) Preparation of polyethersulfone casting solution.

[0023] Polyethersulfone resin, sulfonated polyethersulfone resin, alkylamide, nano zirconium oxide powder, additives, and polyvinyl pyrrolidone were added to the reaction kettle in order by weight, and stirred for 1 hour with a stirrer until the dispersion liquid was transparent, and the rotation speed was 200-300 rpm. After that, the vacuum was evacuated to an absolute pressure of 1-2 Pa, and the mixture was allowed to stand for 1-2 hours in a vacuum environment until no bubbles were generated on the surface of the casting liquid.

[0024] (2) Preparation of polyethersulfone primary filter membrane.

[0025] Under constant temperature and humidity conditions, the casting solution is transferred to a roller, a film or a steel belt, and induced to undergo phase transformation in a non-solvent atmosphere to obtain a primary filter membrane. In this process, the primary membrane is in the non-solvent atmosphere for 2 seconds to 40 minutes.

[0026] Preferably, the constant temperature condition is 50° C., and the constant humidity condition is 85%.

[0027] (3) Shaping of sulfone polymer porous membrane.

[0028] The primary filter membrane is immersed in a coagulation bath, which is deionized water. After the primary filter membrane diffuses in the deionized water, microbubbles are formed on the surface of the membrane. After the gel is solidified, it is subjected to modification, cleaning, drying and shaping processes to obtain a microporous polymer membrane. The primary membrane is in the coagulation bath for 5s-2h, the temperature is 70-80°C, the cleaning time is 3min-8h, and the drying and shaping temperature is 40-250°C.

[0029] Preferably, the primary film is in the coagulation bath for 1 hour at a temperature of 80°C, the water washing time is 3 hours, and the oven temperature is 120°C.

[0030] Beneficial effects:

[0031] 1. The sulfone polymer porous membrane of the present invention has high toughness and mechanical strength, which prolongs the service life, and the production process is simple, easy to control, and highly repeatable, and is suitable for continuous production.

[0032] 2. The sulfone polymer porous membrane of the present invention has high water flux and good permeability, and can be applied to the fields of biomedicine, food and beverage, sewage treatment, electrolytic cells, etc.

[0033] 3. The sulfone polymer porous membrane in the present invention has an average pore size of 1-10um, a thickness of 80-150um, a uniform pore size distribution, and a high pore size consistency, which improves the selectivity and efficiency of the separation process; at the same time, the narrower pore size distribution can provide a more uniform flow channel, thereby reducing the resistance of the fluid passing through the membrane and improving the permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the front side of the sulfone polymer porous membrane prepared according to Example 1 at a magnification of 2000.

[0035] Figure 2 This is a scanning electron microscope image of the front side of the sulfone polymer porous membrane prepared according to Example 1 at a magnification of 500.

[0036] Figure 3 This is a scanning electron microscope image of the reverse side of the sulfone polymer porous membrane prepared according to Example 1 at a magnification of 2000.

[0037] Figure 4 This is a scanning electron microscope image of the reverse side of the sulfone polymer porous membrane prepared according to Example 1 at a magnification of 1000.

[0038] Figure 5 This is a scanning electron microscope image of the cross section of the sulfone polymer porous membrane prepared according to Example 1 at a magnification of 500. DETAILED DESCRIPTION

[0039] Example

[0040] The technical solution of the present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the examples. Unless otherwise specified, the raw materials in the present invention are all commercially available.

[0041] Example 1

[0042] Example 1 provides a sulfone polymer porous membrane. The raw materials of the sulfone polymer porous membrane, by weight, include 10 parts of polyethersulfone resin, 9 parts of sulfonated polyethersulfone resin, 56 parts of N,N-dimethylformamide, 14 parts of additives, 1 part of nano zirconium oxide powder, and 10 parts of polyvinyl pyrrolidone K30.

[0043] The preparation method of the sulfonated polyethersulfone resin is as follows: 15 g of the polyethersulfone resin is added into 200 mL of dichloromethane, and then 15 mL of chlorosulfonic acid is added at a stirring rate of 800 r / min, and the mixture is reacted for 5 hours.

[0044] The nano zirconium oxide powder is KH 570 modified nano zirconium oxide powder, the average particle size of the nano zirconium oxide powder is 30 nm, and the nano zirconium oxide powder is purchased from Shanghai Yingcheng New Materials Co., Ltd.

[0045] The auxiliary agent is a homopolymer of PEG200 and 2-furan methanol, and the weight ratio of the homopolymer of PEG200 and 2-furan methanol is 1:1.

[0046] This embodiment also provides a method for preparing the sulfone polymer porous membrane as described above, comprising the following steps:

[0047] (1) Polyethersulfone resin, sulfonated polyethersulfone resin, N,N-dimethylformamide, nano zirconium oxide powder, additives, and polyvinyl pyrrolidone were added to a reaction kettle in order by weight, and stirred for 1 hour with a stirrer until the dispersion liquid was transparent, and the rotation speed was 300 rpm. After that, the mixture was evacuated to an absolute pressure of 1 Pa and allowed to stand for 1 hour in a vacuum environment until no bubbles were generated on the surface of the casting liquid.

[0048] (2) The casting solution is coated on a smooth and clean glass plate and placed in an air atmosphere with an ambient temperature of 50° C. and a relative humidity of 70% for 20 minutes to obtain a primary film.

[0049] (3) The primary membrane was immersed in a coagulation bath at 80°C for 1 hour. The coagulation bath was deionized water. After the primary membrane was diffused in the deionized water, microbubbles formed on the surface of the membrane. The membrane was then immersed in water for 1 hour. The membrane was then placed in an oven for drying and setting for 5 hours. The oven temperature was 110°C.

[0050] Example 2

[0051] Example 2 provides a sulfone polymer porous membrane. The raw materials of the sulfone polymer porous membrane, by weight, include 10 parts of polyethersulfone resin, 6 parts of sulfonated polyethersulfone resin, 67 parts of N,N-dimethylformamide, 9 parts of additives, 2 parts of nano zirconium oxide powder, and 8 parts of polyvinyl pyrrolidone K30.

[0052] The preparation method of the sulfonated polyethersulfone resin is as follows: 15 g of the polyethersulfone resin is added into 200 mL of dichloromethane, and then 15 mL of chlorosulfonic acid is added at a stirring rate of 800 r / min, and the mixture is reacted for 5 hours.

[0053] The nano zirconium oxide powder is KH 570 modified nano zirconium oxide powder, the average particle size of the nano zirconium oxide powder is 30 nm, and the nano zirconium oxide powder is purchased from Shanghai Yingcheng New Materials Co., Ltd.

[0054] The auxiliary agent is a homopolymer of PEG200 and 2-furan methanol, and the weight ratio of the homopolymer of PEG200 and 2-furan methanol is 1:1.

[0055] This embodiment also provides a method for preparing the sulfone polymer porous membrane as described above, comprising the following steps:

[0056] (1) Polyethersulfone resin, sulfonated polyethersulfone resin, N,N-dimethylformamide, nano zirconium oxide powder, additives, and polyvinyl pyrrolidone were added to a reaction kettle in order by weight, and stirred for 1 hour with a stirrer until the dispersion liquid was transparent, and the rotation speed was 300 rpm. After that, the mixture was evacuated to an absolute pressure of 1 Pa and allowed to stand for 1 hour in a vacuum environment until no bubbles were generated on the surface of the casting liquid.

[0057] (2) The casting solution is coated on a glass plate and placed in an air atmosphere with an ambient temperature of 50° C. and a relative humidity of 70% for 10 minutes to obtain a primary film.

[0058] (3) The primary membrane was immersed in a 70°C coagulation bath for 1 hour. The coagulation bath was deionized water. After the primary membrane was diffused in the deionized water, microbubbles formed on the surface of the membrane. The membrane was then immersed in water for 1 hour. The membrane was then placed in an oven for drying and setting for 5 hours. The oven temperature was 100°C.

[0059] Example 3

[0060] Example 3 provides a sulfone polymer porous membrane. The raw materials of the sulfone polymer porous membrane, by weight, include 10 parts of polyethersulfone resin, 3 parts of sulfonated polyethersulfone resin, 66 parts of N,N-dimethylformamide, 15 parts of additives, 1 part of nano zirconium oxide powder, and 7 parts of polyvinyl pyrrolidone K30.

[0061] The preparation method of the sulfonated polyethersulfone resin is as follows: 15 g of the polyethersulfone resin is added into 200 mL of dichloromethane, and then 15 mL of chlorosulfonic acid is added at a stirring rate of 800 r / min, and the mixture is reacted for 5 hours.

[0062] The nano zirconium oxide powder is KH 570 modified nano zirconium oxide powder, the average particle size of the nano zirconium oxide powder is 30 nm, and the nano zirconium oxide powder is purchased from Shanghai Yingcheng New Materials Co., Ltd.

[0063] The auxiliary agent is a homopolymer of PEG200 and 2-furan methanol, and the weight ratio of the homopolymer of PEG200 and 2-furan methanol is 1:1.

[0064] This embodiment also provides a method for preparing the sulfone polymer porous membrane as described above, comprising the following steps:

[0065] (1) Polyethersulfone resin, sulfonated polyethersulfone resin, alkylamide, nano zirconium oxide powder, additives, and polyvinyl pyrrolidone were added to a reaction kettle in order by weight, and stirred for 1 hour with a stirrer until the dispersion liquid was transparent, and the rotation speed was 300 rpm. After that, the mixture was evacuated to an absolute pressure of 1 Pa and allowed to stand for 1 hour in a vacuum environment until no bubbles were generated on the surface of the casting liquid.

[0066] (2) The casting solution is coated on a smooth and clean glass plate and placed in an air atmosphere with an ambient temperature of 50° C. and a relative humidity of 70% for 40 minutes to obtain a primary film.

[0067] (3) The primary membrane was immersed in a 70°C coagulation bath for 2 h. The coagulation bath was deionized water. After the primary membrane was diffused in the deionized water, microbubbles formed on the surface of the membrane. The membrane was then immersed in water for 6 h. The membrane was then placed in an oven for drying and setting for 5 h. The oven temperature was 120°C.

[0068] In the sulfone polymer porous membrane prepared in Examples 1-3, the pore sizes of the upper surface and the lower surface have the following characteristics: the pores with a pore size of more than 10 microns account for 1-5% of the total number of pores, the pores with a pore size of 5-10 microns account for 90-95% of the total number of pores, and the pores with a pore size of less than 5 microns account for the remainder of the total number of pores, wherein the total number of pores with a pore size of more than 10 microns, pores with a pore size of 5-10 microns, and pores with a pore size of less than 5 microns is 100. The pore size of the sulfone polymer porous membrane is tested by a PMI pore size tester.

[0069] Comparative Example 1

[0070] A sulfone polymer porous membrane, the specific implementation methods of its preparation raw materials and preparation method are the same as those in Example 1, except that: the raw materials of the sulfone polymer porous membrane, by weight, include 20 parts of polyethersulfone resin, 57 parts of N,N-dimethylformamide, 10 parts of additives, 1 part of nano zirconium oxide powder, and 12 parts of polyvinyl pyrrolidone K30.

[0071] The auxiliary agent is PEG200.

[0072] Comparative Example 2

[0073] A sulfone polymer porous membrane, the specific implementation methods of its preparation raw materials and preparation method are the same as those in Example 1, except that: the raw materials of the sulfone polymer porous membrane, by weight, include 5 parts of polyethersulfone resin, 15 parts of sulfonated polyethersulfone resin, 50 parts of N,N-dimethylformamide, 14 parts of additives, 2 parts of nano zirconium oxide powder, and 14 parts of polyvinyl pyrrolidone K30.

[0074] Comparative Example 3

[0075] A sulfone polymer porous membrane, the specific implementation methods of its preparation raw materials and preparation method are the same as those in Example 1, except that: the raw materials of the sulfone polymer porous membrane, by weight, include 5 parts of polyethersulfone resin, 5 parts of sulfonated polyethersulfone resin, 60 parts of N,N-dimethylformamide, 14 parts of additives, 3 parts of nano zirconium oxide powder, and 13 parts of polyvinyl pyrrolidone K30.

[0076] The auxiliary agent is a homopolymer of PEG200 and 2-furan methanol, and the weight ratio of the homopolymer of PEG200 and 2-furan methanol is 1:3.

[0077] Performance Testing Methods

[0078] 1. Bubble point pressure: Bubble point pressure refers to the surface tension of a liquid film formed when a liquid passes through a filter membrane. The surface tension of the liquid is equal to the pressure generated by the height of the siphon liquid column. The bubble point pressure test was performed on Examples 1-3 and Comparative Examples 1-3, using purified water as the test water, and the test temperature was 20-25°C. During the test, the test water was used to completely soak the membrane in advance, and then the system was pressurized. When the first bubble appeared in the test pool and bubbles appeared continuously, the pressure was immediately stopped, and the bubble point pressure at this time was read. The specific values ​​are shown in Table 1.

[0079] 2. Water flux: Water flux test was conducted on Examples 1-3 and Comparative Examples 1-3. The test method was in accordance with HY / T107-2008. The test conditions were 30 kPa pressure difference. The specific values ​​are shown in Table 1.

[0080] 3. Breaking strength and breaking elongation: The breaking strength of Examples 1-3 and Comparative Examples 1-3 was tested according to HY / T 213-2016. The specific values ​​are shown in Table 1.

[0081] Performance test data

[0082] Table 1

[0083]

Claims

1. A sulfone polymer porous membrane, characterized in that: The raw materials of the sulfone polymer porous membrane include, by weight, 5-30 parts of polyethersulfone resin, 3-15 parts of sulfonated polyethersulfone resin, 30-85 parts of alkylamide, 1-15 parts of auxiliary agent, and 0.1-5 parts of nano zirconium oxide powder; the preparation method of the sulfonated polyethersulfone resin is: adding the polyethersulfone resin to dichloromethane, then adding chlorosulfonic acid at a certain stirring rate, and reacting for a certain time.

2. A sulfone polymer porous membrane according to claim 1, characterized in that: The weight ratio of the polyethersulfone resin to the sulfonated polyethersulfone resin is 1.1-4:

1.

3. A sulfone polymer porous membrane according to claim 1, characterized in that: The alkylamide includes at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

4. A sulfone polymer porous membrane according to claim 1, characterized in that: The auxiliary agent is at least one of polyethylene glycol, polypropylene glycol, polyethylene glycol bisbenzophenone-2-carboxylate, tetrahydrofuran and neopentyl glycol polymer, polybutylene glycol, and a homopolymer of 2-furanmethanol.

5. A sulfone polymer porous membrane according to claim 1, characterized in that: The average particle size of the nano zirconium oxide powder is 10-50nm.

6. A sulfone polymer porous membrane according to claim 5, characterized in that: The nano zirconium oxide powder is nano zirconium oxide powder modified by a silane coupling agent.

7. A sulfone polymer porous membrane according to any one of claims 1 to 6, characterized in that: The raw materials of the sulfone polymer porous membrane also include 8-20 parts by weight of polyvinyl pyrrolidone.

8. A sulfone polymer porous membrane according to claim 7, characterized in that: The thickness of the sulfone polymer porous membrane is 80-150 μm; further, the thickness of the sulfone polymer porous membrane is 110-120 μm.

9. A method for preparing a sulfone polymer porous membrane according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Preparation of polyethersulfone casting solution: polyethersulfone resin, sulfonated polyethersulfone resin, alkylamide, nano zirconium oxide powder and additives are added to a reaction kettle in order according to weight, stirred with a stirrer, and allowed to stand for 1-2 hours under a vacuum environment until no bubbles are generated on the surface of the casting solution; (2) Preparation of polyethersulfone primary filter membrane; (3) Shaping of sulfone polymer porous membrane.

10. Use of the sulfone polymer porous membrane according to any one of claims 1 to 8 in the fields of medical devices, water treatment, and battery separators.